Construction of Large‐Scale Ultrathin Graphitic Carbon Nitride Nanosheets by a Hydrogen‐Bond‐Assisted Strategy for Improved Photocatalytic Hydrogen Production and Ciprofloxacin Degradation Activity. Issue 17 (5th August 2016) - Xing, Weinan; Chen, Gang; Li, Chunmei; Sun, Jingxue; Han, Zhonghui; Zhou, Yansong; Hu, Yidong; Meng, Qingqiang
Abstract: Two‐dimensional nanosheets have attracted attention because of their fascinating properties in areas such as photocatalysis, sensors, and energy storage. Herein, a facile hydrogen‐bond‐assisted approach was designed to prepare graphitic carbon nitride (g‐C3 N4 ) with large‐scale ultrathin nanosheets. Compared with previous methods, this method is simple, economical, and eco‐friendly. The as‐prepared ultrathin g‐C3 N4 nanosheets have a few‐layer thickness of 2–3 nm and exhibit a significantly enhanced photocatalytic activity in both H2 production and ciprofloxacin degradation under visible light compared to pristine g‐C3 N4 . The enhanced photocatalytic activity is attributed to the minimal sheet thickness, high surface area, increased band gap, outstanding electron transport ability, and long charge‐carrier lifetime. In addition, the possible formation mechanism, transfer and separation behavior of the charge carriers, and the photocatalytic mechanism are discussed. This work presents a new hydrogen‐bond‐assisted self‐assembly strategy for the preparation of ultrathin g‐C3 N4 nanosheets for application in photocatalysis. Abstract : Between the sheets : A facile hydrogen‐bond‐assisted approach was designed to prepare graphitic carbon nitride (g‐C3 N4 ) as large‐scale ultrathin nanosheets. The as‐prepared ultrathin g‐C3 N4 nanosheets have a few‐layer thickness of 2–3 nm and exhibit significantly enhanced photocatalytic activity in both H2 production and ciprofloxacin degradation under visible light compared to pristine g‐C3 N4 .